Analysis of Online Media Framing in the Russia-Ukraine Conflict: Comparison of BBC Indonesia and CNN Indonesia - Bisri, Muhammad Hasan; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Russia-Ukraine conflict has emerged as a pivotal global issue, significantly reshaping the geopolitical landscape. Specific Background: This study examines how mass media outlets, particularly BBC Indonesia and CNN Indonesia, frame their coverage of the conflict, emphasizing the role of media narratives in public perception. Knowledge Gap: While existing research highlights media influence in conflict reporting, there is limited comparative analysis focusing on Indonesian media and their unique framing techniques. Aims: The research aims to explore the differences in narrative construction and coverage strategies employed by BBC Indonesia and CNN Indonesia regarding the Russia-Ukraine conflict. Results: Through a systematic review of news reports, the findings reveal distinct approaches in the two media outlets, characterized by variations in perspective, source selection, and information presentation styles, despite a shared commitment to accuracy. Novelty: This study contributes new insights into the comparative framing of international conflicts by Indonesian media, underscoring the importance of contextual factors in shaping news narratives. Implications: The results suggest that understanding these framing differences is crucial for evaluating media influence on public opinion and discourse surrounding global conflicts, potentially guiding future research and media literacy initiatives in Indonesia and beyond. Highlights: Comparative Analysis: The study fills a gap in research by comparing the framing techniques of two prominent Indonesian media outlets, revealing unique narrative constructions. Diverse Approaches: Findings indicate that BBC Indonesia and CNN Indonesia utilize different perspectives and source selections, affecting how the conflict is portrayed. Impact on Public Discourse: Understanding these framing differences is essential for assessing media influence on public opinion regarding international conflicts. Keywords - Russia-Ukraine conflict, media framing, BBC Indonesia, CNN Indonesia, public perception